2015
DOI: 10.1016/j.ecresq.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Technology-assisted interventions for parents of young children: Emerging practices, current research, and future directions

Abstract: Technology can potentially expand the reach and cut the costs of providing effective, evidence-based interventions. This paper reviews existing publications that describe the application and evaluation of technology-assisted interventions for parents of young children. A broad review of the early childhood literature revealed 48 studies describing technology-assisted parent education and interventions. Across these studies, multiple forms of technology were used, including web-based platforms, discussion forum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 60 publications
3
153
0
3
Order By: Relevance
“…These programs are in different stages of implementation and validation, which was not assessed in this review. Previous metaanalysis or systematic reviews (Cushing & Steele, 2010;Hall & Bierman, 2015;MacDonell & Prinz, 2016) have already contributed to evaluate the effectiveness of technology-based programs targeting specific conditions, but more research is necessary. An optimistic perspective arises from the meta-analysis carried out by Wantland, Portillo, Holzemer, Slaughter, & McGhee (2004), which found that the use of web-based interventions for adults with chronic conditions showed larger effect sizes than the face-to-face programs in terms of the acquisition of knowledge and behaviour change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These programs are in different stages of implementation and validation, which was not assessed in this review. Previous metaanalysis or systematic reviews (Cushing & Steele, 2010;Hall & Bierman, 2015;MacDonell & Prinz, 2016) have already contributed to evaluate the effectiveness of technology-based programs targeting specific conditions, but more research is necessary. An optimistic perspective arises from the meta-analysis carried out by Wantland, Portillo, Holzemer, Slaughter, & McGhee (2004), which found that the use of web-based interventions for adults with chronic conditions showed larger effect sizes than the face-to-face programs in terms of the acquisition of knowledge and behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review on technology-assisted interventions for parents of young children (Hall & Bierman, 2015) identified a wide range of high-level feasibility programs using diversified technology applications. These programs include mostly educational materials and behavioral strategies to promote positive parenting, as well as a variety of objectives, including universal programs and indicated interventions targeting developmental and behavioral problems.…”
Section: Palavras-chave: Saúde; Tecnologia Da Informação; Responsabilmentioning
confidence: 99%
“…For example, a recent consumer preference study (Metzler et al, 2012) found that low intensity, self-directed formats, including television, the internet, and written materials, were rated as the most preferred format for receiving parenting information, over and above more intensive methods such as professional consultations, home visits, and parenting groups. Similarly, a review by Hall and Bierman (2015) found that roughly half of the parents interviewed within various studies reported a preference for accessing advice through the internet (Rothbaum, Martland, & Jannsen, 2008;Walker et al, 2012).…”
Section: The Evidence For Low Intensity and Web-based Psychological Tmentioning
confidence: 99%
“…There are myriad parent-focused websites publicly available that contain educational material, general parenting advice, and in some cases discussion forums to foster peer learning and support (e.g. Na & Chia, 2008;Plantin & Daneback, 2009), and which are generally well-received by parents (Hall & Bierman, 2015). Parents also commonly congregate through social media, such as Facebook, to share parenting ideas, ask for advice, and receive support from others, although the benefits and adverse effects of these practices are still not clear.…”
Section: The Evidence For Low Intensity and Web-based Psychological Tmentioning
confidence: 99%
See 1 more Smart Citation